Disability and job mismatches in the Australian labour market - Melanie Jones; Kostas Mavromaras; Peter Sloane; Zhang Wei (Institute for the Study of Labor (IZA), 2011)
We examine the relationship between disability, job mismatch, earnings and job satisfaction, using panel estimation on data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey (2001-2008). While we do not find any relationship between work-limiting disability and over-skilling, it appears that there is a positive relationship between work-limiting disability and over-education, which is consistent with disability onset leading to downward occupational movement, at least in relative terms. We find a negative correlation between work-limiting disability and both earnings and job satisfaction. However, there is only evidence of a causal relationship in terms of the latter, where the impact of disability is found to be multifaceted.
urn:nbn:de:101:1-2012010913722
Keywords: I0; J2; J3; J7; J24; J31; 330; job mismatch; disability; earnings; job satisfaction; Behinderte Arbeitskräfte; Berufliche Integration; Lohnniveau; Arbeitszufriedenheit; Australien